Growth of Probiotic Bacteria (Bifidobacterium bifidum and Lactobacillus plantarum) in Medium Mixed Taro Rope (Colocasia esculenta L. Schott var Boring) and Soybean Powder - Joni Kusnadi; Kartika Cahyania Pratiwi (Natural B, Journal of Health and Environmental Sciences, 2013)
This study was aimed to determine the effect of mix proportions of soy powder and taro flour on the growth of probiotic bacteria Bifidobacterium bifidum and Lactobacillus plantarum. The experiments were performed using a randomized block design with two factors: the proportion of taro flour: soybean powder on the fermentation medium (6%: 9%, 7.5%: 7.5%, and 8%: 7%) and type of probiotic bacteria (B. bifidum and L. plantarum) with 3 replications. The results showed that treatment of taro flour and soybean powder on fermentation medium significantly (α = 0.05) decrease the degree of acidity (pH). While the treatment of probiotic (B. bifidum and L. plantarum) isolates significantly (α = 0.05) increase the total BAL, reduced the degree of acidity (pH), decreased total sugar and starch content. There is no interaction between the two treatments. The best treatment was obtained from the proportion of taro flour fermentation medium: soybean powder of 8%: 7% for L. plantarum isolates with the total L. plantarum of 4,24x1010CFU/ml, the degree of acidity (pH) of 3.32, and total sugar and starch content of 19.29%, 6.53%, respectively.